Effect of duplex drugs linking 2′-deoxy-5-fluorouridine (5-FdU) with 3′-C-ethynylcytidine (ECyd) on hepatoblastoma cell lines - Eicher, Carmen; Dewerth, Alexander; Ellerkamp, Verena; Fuchs, Joerg; Schott, Sarah; Armeanu-Ebinger, Sorin (Pediatric surgery international, 2013)
Duplex drugs are promising anticancer agents. After in vivo cleavage into active nucleoside analogues, they exert their anti-tumour activity with reduced toxicity and side effects. Here we evaluated the impact of two duplex drugs on the viability of hepatoblastoma (HB) cells lines and their toxicity against human fibroblasts.
Published online: 28 November 2012
Gesehen am 08.01.2021